Seasonal mixing from intermittent flow drives concentration‐discharge behaviour in a stream affected by coal mine drainage. Issue 17 (24th June 2020) - Shaw, Meaghan; Yazbek, Lindsey; Singer, David; Herndon, Elizabeth
Abstract: Abandoned mining operations continue to severely degrade many ecosystems worldwide by releasing acidic water and/or heavy metals into surface and groundwater. Contaminant concentrations in affected streams vary with discharge in patterns that reflect both geochemical reactions and variable mixing of contaminated and non‐contaminated waters. However, controls on concentration‐discharge (C‐Q) patterns remain unclear, particularly for constituents that experience changing solubility across redox and pH gradients. Understanding the C‐Q behaviour of contaminants aids in predicting both downstream transport and effects on aquatic life under variable flow. Here, we examined the C‐Q behaviours of non‐reactive (Na, K, Ca, Mg, Cl − ) and reactive (Fe, Mn, Al, H +, SO4 2− ) solutes in a stream contaminated with acid mine drainage in northeastern Ohio, USA. Concentration‐discharge patterns at the watershed outlet primarily reflected mixing of contaminated baseflow with intermittent inputs of high pH water draining from a passive limestone treatment system into the stream. The treatment system acted as an ephemeral tributary that mitigated contamination in the stream by diluting solutes, raising pH, and driving metal precipitation, but only when flow was present during wet seasons. Consequently, AMD‐derived reactive solutes (H +, Fe, Mn, Al) decreased with increasing stream discharge while relatively conservative solutes (e.g., Ca, Mg, K, Na) decreased only slightly or were chemostatic. This study highlights both the unique C‐Q patterns of reactive solutes when compared to those of non‐reactive solutes and the potential for intermittent streams to control C‐Q behaviour in headwater catchments. Abstract : Seasonal inputs of effluent from a treatment system into a contaminated stream drive concentration‐discharge (C‐Q) behaviour in a headwater catchment impaired by coal mine drainage. The degree to which mixing drives C‐Q behaviour depends on how sensitive a particular solute is to changes in redox and pH. This study highlights how stream connectivity is a critical component regulating stream chemistry, particularly for reactive solutes or solutes distributed heterogeneously within a catchment.